The Impact of Security, Digital Financial Literacy, and Trust on Cryptocurrency Investment Experiences - Jul Aidil Fadli (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the influence of security and digital financial literacy on cryptocurrency investment with trust as a mediating variable, especially among the younger generation as dominant investors. Quantitative methods were used through a survey of 297 active cryptocurrency investors in Indonesia, analyzed using the Structural Equation Model with the Partial Least Squares approach. The results showed that security has a positive effect on trust in cryptocurrency, which plays an important role in increasing investor confidence in this asset. Digital financial literacy and trust also have a positive effect on cryptocurrency investment experience, emphasizing the importance of understanding digital finance in the new financial era. In addition, trust mediates the effect of security on investment experience, serving as a bridge between security and a good investment experience. Thus, to improve investment experience, investors need to have a good understanding of digital finance and a high level of trust in cryptocurrency. Trust is a key factor in shaping a positive investment experience and driving further adoption of cryptocurrency.